Characterization of Volatile Compounds and Odorants in Different Sichuan Pepper Varieties in Tallow Hotpot - Wenhua Li; Qiaojun Wang; Huilin Huan; Gangcheng Wu; Qingzhe Jin; Youfeng Zhang; Xingguo Wang (Foods, 2025)
Sichuan pepper plays a vital role in enhancing the flavor of hotpot. However, the specific flavor compounds involved are still unclear. In this study, the key aroma components of Sichuan pepper tallow hotpot were explored. Six aroma attributes were evaluated by quantitative descriptive sensory analysis (QDA). Gas chromatography–mass spectrometry (GC-MS) identified 56 compounds. Among them, a total of 27 aroma-active compounds were identified by gas chromatography–olfactometry (GC-O) and aroma extract dilution analysis (AEDA). Sixteen aroma-active compounds were determined using odor activity values (OAVs) ≥ 1. Linalool, linalyl acetate, D-limonene, sabinene, β-myrcene, eucalyptol, α-terpineol, terpinen-4-ol, acetic acid, (E,E)-2,4-decadienal, (E)-2-heptenal, and others were identified as the key aroma compounds. Chemometrics analysis indicated that the aroma of green Sichuan pepper tallow hotpot was green, and the aroma of different red Sichuan pepper tallow hotpots varied significantly. The research results serve as a foundation for the quality control and production of the hotpot industry.